ANALISIS WAKTU TEMU KEMBALI ARSIP PELAYANAN ADMINISTRASI RUMAH SAKIT MATARAM - Melinda; Muhammad Aditya Rachman; Muhammad Habibullah Aminy; Lale Ajeng Khalifatun Wardani; Slamet Mardiyanto Rahayu (LPPM, Akademi Administrasi Rumah Sakit Mataram, 2026)
This study aims to analyze the efficiency of records management by measuring the retrieval time of administrative service archives at Mataram Hospital as an effort to improve the quality of healthcare services. Using a descriptive quantitative method with an observational approach to 50 document request transactions in April 2026, the results showed that the average time required to retrieve archives was 13.5 minutes, which still exceeds the threshold of the Standard Operating Procedure (SPO) set at a maximum of 10 minutes, with a standard fulfillment rate of only 60%. The constraint analysis revealed that this delay was triggered by limited storage capacity causing overcrowded document arrangement, a high frequency of misplaced documents (misfile) due to undisciplined use of outguides (tracers) during peak hours, and suboptimal archive room lighting. The impact of this condition directly extends queues at the administration counter and hinders the speed of both managerial and medical decision-making. As a strategic solution, this study recommends reorganizing the archive layout to be more ergonomic, conducting periodic disposal of inactive records, and accelerating the transformation toward a digital archiving system to minimize dependence on physical searching. The implementation of these solutions is expected to ensure data security, enhance patient safety through rapid information availability, and optimize the overall quality of administrative services at Mataram Hospital.